Circularly Polarized Luminescence from Inorganic Materials: Encapsulating Guest Lanthanide Oxides in Chiral Silica Hosts. Issue 25 (6th February 2018) - Sugimoto, Masumi; Liu, Xin‐Ling; Tsunega, Seiji; Nakajima, Erika; Abe, Shunsuke; Nakashima, Takuya; Kawai, Tsuyoshi; Jin, Ren‐Hua
Abstract: Recently, circularly polarized luminescence (CPL)‐active systems have become a very hot and interesting subject in chirality‐ and optics‐related areas. The CPL‐active systems are usually available by two approaches: covalently combining a luminescent centre to chiral motif or associating the guest of luminescent probe to a chiral host. However, all the chiral components in CPL materials were organic, although the luminescent components were alternatively organics or inorganics. Herein, the first totally inorganic CPL‐active system by "luminescent guest–chiral host" strategy is proposed. Luminescent sub‐10 nm lanthanide oxides (Eu2 O3 or Tb2 O3 ) nanoparticles (guests) were encapsulated into chiral non‐helical SiO2 nanofibres (host) through calcination of chiral SiO2 hybrid nanofibres, trapping Eu 3+ (or Tb 3+ ). These lanthanide oxides display circular dichroism (CD) optical activity in the ultraviolet wavelength and CPL signals around at 615 nm for Eu 3+ and 545 nm for Tb 3+ . This work has implications for inorganic‐based CPL‐active systems by incorporation of various luminescent guests within chiral inorganic hosts. Abstract : Sand in the tartan kilt? Inorganic materials assembled with chiral silica hosts and luminescent oxide guests were synthesized by entrapping lanthanide ions into chiral silica loaded with polyethyleneimine/tartaric acid and subsequently calcined at 900 °C. The lanthanide oxide nanoparticles of Eu2 O3 and Tb2 O3 formed in the restricted space of the chirald ‐ andl ‐silica hosts displayed chiral signals both in circular dichroism (CD) and circularly polarized luminescence (CPL).